1997
DOI: 10.1136/jcp.50.12.985
|View full text |Cite
|
Sign up to set email alerts
|

A review of 50 consecutive cytology cell block preparations in a large general hospital.

Abstract: Aims-To review consecutive cell block preparations of cytological specimens in a large general hospital. Methods-50 cell blocks were made over an 18 month period in which about 1900 fine needle aspirations (FNAs) were performed. The aspirator was a cytologist or, for image guided FNAs, a radiologist with a cytologist at hand to collect the specimen. Forty eight cell blocks were from FNAs and two were from serous fluids. Results-The cellularity of the cell blocks was inadequate in only four preparations. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 3 publications
0
48
0
Order By: Relevance
“…Cotton block method is another alternative by which cytomorphological features in body fluids can be studied. 11,[15][16][17] In this study, all three malignancies found in the smears and blocks were adenocarcinomas. This comprised 8.1 % of cases (3/37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton block method is another alternative by which cytomorphological features in body fluids can be studied. 11,[15][16][17] In this study, all three malignancies found in the smears and blocks were adenocarcinomas. This comprised 8.1 % of cases (3/37).…”
mentioning
confidence: 99%
“…So, different antibodies serve as reliable markers in the differential diagnosis of reactive mesothelial cells, adenocarcinona and malignant mesothelioma in serous effusions. [7][8][9][10][11][12][13][14] This diagnostic dilemma can be furthered settled by staining with PAS stain, D-PAS, Alcian blue and Hyranuronidase alcian blue. Introduction of CK 5/6 and calretinin helps in differentiating mesothelioma from adenocarcinoma.…”
mentioning
confidence: 99%
“…Delay in the diagnosis when compared to conventional smears due to additional time for CB preparation, [17] risk of losing material during processing and increased cost are some of the drawbacks. [26] Some authors like Wojick et al found that the additional studies of cell blocks is of little benefit after a study CB in a case of hepatic hydatid cyst showing protoscolices, recurrent SCC of oral cavity. [23] They suggested that CB is a forgotten tool these days and reemphasized it's utility in CB was non-contributory.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the use which aid in the cytological examination. [26] Though CB complements CS diagnosis with added advantage of better architecture, availability of material for special stains and IHC in many cases, CB also has certain disadvantages. Delay in the diagnosis when compared to conventional smears due to additional time for CB preparation, [17] risk of losing material during processing and increased cost are some of the drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A larger number of cells in a compacted area of one section on a slide glass, compared with sparse cells on the smear, leads to a more accurate diagnosis. Furthermore, paraffin sections can be used later for immunocytochemical diagnosis and clonal analysis.…”
Section: Discussionmentioning
confidence: 99%